Strategies to cope claustrophobia during magnetic resonance imaging examination - Zaidi, Syed Amir Raza; Masood, Kamran; Khanzada, Usman; Adil, Syed Omair; Hussain, Munawar (International Journal of Research in Medical Sciences, 2019)
Background: Claustrophobia associated with MRI scan is a well-recognized problem all over the world. The unpleasant psychological experience during MRI can lead to premature cancellation of the study resulting in non-interpretable data. In addition, performing future studies on the claustrophobic patient may not be possible leading to non-utilization of an important diagnostic modality. This study was conducted with the aim to determine a cheap and short intervention which can be applicable to small radiology set up as well. Methods: A prospective study was conducted at a tertiary care hospital from October 2016 to December 2016. Accompanying someone was the first strategy used to coped MR imaging claustrophobia followed by placebo (multivitamin), listening Quran and closed eye (blindfold). All those patients who failed to respond in these strategies were finally labeled as an unsuccessful candidate. Listening of Quran was selected as one of the tools as all the patients were Muslims in present study. Results: Among 84 claustrophobic patients, a closed eye was the most successful strategy found effective in (13) 81.2%, followed by placebo 66.7% patients, listening Quran (7) 30.4%, accompanying someone (15) 17.85% while 4% patients remained claustrophobic after application of all strategies. Significant association of accompanying someone and placebo was observed with education (p-value 0.037) and age of the patients (0.016) respectively. Conclusions: In general, placebo, being accompanied by someone and blindfold were found to be the most effective strategies to cope with MRI related claustrophobia. However, the success of these strategies is also dependent on certain factors like age, education status and socioeconomic status of the patients.